Pengaruh Pembelajaran Ilmu Kaligrafi Terhadap Keterampilan Menulis (Maharah Kitabah) - Arum Tri Budi Arti; Khuzaimah Alfi Syahrina; Rahmatunnisak Rahmatunnisak (Yayasan Haiah Nusratul Islam, 2024)
Calligraphy is a beautiful and correct way of writing Arabic in accordance with the rules of writing. The science of calligraphy is not only concerned with the beauty of writing, but also concerned with the correctness of writing in accordance with the rules of writing. while Maharah Kitabah or writing skill is the ability to express, express and describe ideas, thoughts, and ideas in written form. Between learning calligraphy is very closely related to writing skills or maharah kitabah, so that from this linkage learning calligraphy has a great influence on maharah kitabah or writing skills. Therefore, the purpose of this study is to find out what influences arise from learning calligraphy on Maharah Kitabah. This research is qualitative by using literature study using descriptive analysis method. The results of the study show that the influence of learning calligraphy on maharah kitabah or writing skills, including improving Arabic writing according to the rules of writing, and learning calligraphy can beautify Arabic writing, so that writing has aesthetic and spiritual values, and also trains someone to describe his ideas and thoughts in a structured written form.